Changing Pattern of Agricultural Land Use in Sonbhadra District, U.P. - Singh, S.K.; Sharma, V.N. (National Geographical Journal of India, 2022)
The land available for cultivation is important for the people who engaged in agricultural activities. Sonbhadra district has 21.59 per cent net sown of the total land where a number of crops are grown by the farmers. The land occupied by different crop are foodgrains (61.84 per cent) followed by pulses (19.66 per cent), oil seeds (7.62 per cent), commercial crops (2.19 per cent), others crops (8.50 per cent) and industrial crops (0.19 per cent). It provides food and various industrial raw materials to feed the agro-based industries. The main objective of the paper is to present an agricultural land use scenario in Sonbhadra district during 1995 to 2015